Effects of low-phosphorus diets on phosphorus balance, plasma concentrations of 25-hydroxyvitamin D3, and carboxy-terminal collagen crosslinks during the transition period in dairy cows - P. Keanthao; R.M.A. Goselink; J. Dijkstra; A. Bannink; J.T. Schonewille (Journal of Dairy Science)
ABSTRACT: Our aim was to determine the effects of P intake on P balance, serum parathyroid hormone (PTH) levels, and bone resorption during the final 4 wk prepartum and the first 8 wk of lactation. Sixty pregnant multiparous Holstein Friesian dairy cows were assigned to a randomized block design with repeated measurements and dietary treatments arranged according to a 2 × 2 factorial design. The experimental diets contained 3.6 (high phosphorus [HP]) or 2.2 (low phosphorus [LP]) g P/kg DM during the dry period (Dry-HP and Dry-LP, respectively), and 3.8 or 2.9 g P/kg DM during 56 d after calving (Lac-HP and Lac-LP, respectively). The level of dietary P of Dry-LP, expressed as g/kg DM, was 18% greater than recommended by the Dutch Central Bureau for Livestock Feeding (The Hague, the Netherlands), whereas the P content of Lac-LP was, across the 8 wk of lactation, 24% lower than recommended. Both P intake and fecal P excretion decreased in the dry period to increase again in subsequent lactation. Cows fed high dietary P excreted more P in the feces than cows fed low dietary P pre- and postpartum. Cows in both Dry-HP and Dry-LP were in positive P balance in the dry period. Cows in both Lac-LP and Lac-HP were in negative P balance after calving, with the negative P balance being more pronounced in Lac-LP than in Lac-HP. Serum concentrations of PTH and apparent total-tract OM and NDF digestibility were neither affected by any 2-way or 3-way interaction between time of sampling and dietary treatments nor by the P concentration of the experimental diets during the pre- and postpartum period. Before calving, serum carboxy-terminal collagen crosslink (CTX) concentrations were basically similar between Dry-HP and Dry-LP. After calving, serum CTX concentrations increased, with a more pronounced increase when Lac-LP was fed compared with Lac-HP. The results suggest that when feeding diets containing low P (2.9 g/kg DM) postpartum, cows excreted less P in the feces than at recommended dietary P (3.8 g P/kg DM) without a negative impact on OM and NDF digestibility. The increase in serum CTX concentrations, without increasing serum PTH concentrations upon feeding low P, indicate a prominent role of bone resorption to meet P demands in the first 8 wk postpartum. The present trial focused on the final 4 wk of gestation and the subsequent 8 wk of lactation, but long-term effects of low dietary P during early lactation on serum PTH and on bone P dynamics in mid and late lactation need to be further investigated.